# Solve the following equations:(x2 – y2)dx – 2xydy = 0

Given differential equation is:

(x2 – y2)dx – 2xydy = 0

(x2 – y2)dx = 2xydy ……(1)

Homogeneous equation: A equation is said to be homogeneous if f(zx,zy) = znf(x,y) (where n is the order of the homogeneous equation).

Let us assume     f(zx,zy) = z0f(x,y)

So, given differential equation is a homogeneous differential equation.

We need a substitution to solve this type of linear equation and the substitution is y = vx.

Let us substitute this in (1) We know that:       Bringing Like variables on same sides we get,   We know that: Integrating on both sides, we get,  ( logC is an arbitrary constant)

Multiplying with -3 on both sides we get,

log|1-3v2| = -3logx + 3logC ( ) ( alogx = logxa) Applying exponential on both sides we get, Since y = vx, we get,     Cross multiplying on both sides we get,

x(x2 – 3y2) = c3

x3 – 3xy2 = K (say any arbitrary constant)

The solution for the differential equation is x3 – 3xy2 = K

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Interactive Quiz on DIfferential CalculusFREE Class  Functional Equations - JEE with ease48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 